2009
DOI: 10.1002/jsfa.3500
|View full text |Cite
|
Sign up to set email alerts
|

Environmental conditions in relation to stress in cherry tomato fruits in two experimental Mediterranean greenhouses

Abstract: BACKGROUND: Considering the economic importance of tomato and its nutritional benefits to human health, a study was conducted on how different environmental factors (temperature, solar radiation and vapour pressure deficit (VPD)) influence hydrogen peroxide detoxification and several stress indicators in cherry tomato (Solanum lycopersicum cv. Naomi) fruits grown in two experimental Mediterranean greenhouses of parral (low-technology) type and multispan (high-technology) type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 44 publications
2
11
0
1
Order By: Relevance
“…At the end of the fruit production cycle, the greenhouse temperatures exceeded the optimum for tomato growth, which is defined as between 23 and 26 °C,54 coinciding with a significant increase in values of solar radiation and VPD, and consequently, in our experiment, certain metabolic as well as physiological disorders could have arisen and affected yield and nutritional quality 7, 55. In a prior study under these conditions, we found a increase in values of lipid peroxidation and antioxidant activity in cherry tomatoes in the third sampling,33 indicating oxidative stress coinciding with the highest values for temperature, solar radiation, and VPD (Fig. 1).…”
Section: Resultssupporting
confidence: 47%
See 2 more Smart Citations
“…At the end of the fruit production cycle, the greenhouse temperatures exceeded the optimum for tomato growth, which is defined as between 23 and 26 °C,54 coinciding with a significant increase in values of solar radiation and VPD, and consequently, in our experiment, certain metabolic as well as physiological disorders could have arisen and affected yield and nutritional quality 7, 55. In a prior study under these conditions, we found a increase in values of lipid peroxidation and antioxidant activity in cherry tomatoes in the third sampling,33 indicating oxidative stress coinciding with the highest values for temperature, solar radiation, and VPD (Fig. 1).…”
Section: Resultssupporting
confidence: 47%
“…However, in both types of greenhouses, the control of the climatic conditions remains a problem, causing environmental stress during the summer months which can influence both yield as well as nutritional quality of the cherry tomato fruits 36. In a previous study,33 we observed that under conditions of high temperatures, solar radiation, and VPD, lipid peroxidation increased and therefore so did oxidative stress, which triggered an antioxidant response based on greater ascorbate synthesis, H 2 O 2 detoxification, and proline accumulation. Also, in this study, we found that the parral greenhouse (low technology), in comparison to the multispan (high technology), reached the severest conditions of environmental stress defined by the high values of the stress indicators and of the antioxidant response.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Similarly, Rosales et al (2009) found that the tomatoes grown in their experimental parral greenhouses showed a significant increase in the total ascorbate concentration during the third sampling with respect to the previous samplings, throughout the productive cycle. These data coincide with the environmental stress provoked by the higher temperature, solar radiation, and VPD.…”
Section: Antioxidant Capacity and Phytonutrientsmentioning
confidence: 65%
“…These data coincide with the environmental stress provoked by the higher temperature, solar radiation, and VPD. Although some studies do not correlate ascorbate accumulation with environmental stress (Adegoroye and Jolliffe, 1983;Hamauzu et al, 1994), others do agree with the results cited, where the climate conditions boosted the ascorbate content as an antioxidant response for acclimation to stress (Dumas et al, 2003;Rosales et al, 2009;Rosales et al, 2011), conferring greater nutritional quality to tomato fruits. In the present work, in all the samples the highest K rate increased both the total phenol concentration as well as that of AsA Red.…”
Section: Antioxidant Capacity and Phytonutrientsmentioning
confidence: 93%